2013
DOI: 10.1128/ec.00316-12
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Novel Preribosomal Complex in Trypanosoma brucei Determined by Fluorescence Resonance Energy Transfer

Abstract: We have previously reported that the trypanosome-specific proteins P34 and P37 form a unique preribosomal complex with ribosomal protein L5 and 5S rRNA in the nucleoplasm. We hypothesize that this novel trimolecular complex is necessary for stabilizing 5S rRNA in Trypanosoma brucei and is essential for the survival of the parasite. In vitro quantitative analysis of the association between the proteins L5 and P34 is fundamental to our understanding of this novel complex and thus our ability to exploit its uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…L5 (GenBank accession no. XM_822569), cerulean-L5, enhanced yellow fluorescent protein (eYFP)-P34, the N and C termini and L18 domain of L5, and the N and C termini and RRM domain of P34 were cloned into pTrcHis-TOPO (Invitrogen) for expression as polyhistidine fusion proteins in TOP10 One Shot cells (Invitrogen), as described previously (16). All of the recombinant protein expression plasmids were confirmed by DNA sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…L5 (GenBank accession no. XM_822569), cerulean-L5, enhanced yellow fluorescent protein (eYFP)-P34, the N and C termini and L18 domain of L5, and the N and C termini and RRM domain of P34 were cloned into pTrcHis-TOPO (Invitrogen) for expression as polyhistidine fusion proteins in TOP10 One Shot cells (Invitrogen), as described previously (16). All of the recombinant protein expression plasmids were confirmed by DNA sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
“…showed that the N-terminal APK-rich domain and the RRM domain of P34 and the L18 domain of L5 are important for the association between P34 and L5 (16). Immune capture assays also showed that 5S rRNA enhances the protein-protein association (11).…”
Section: S Rrna Binds the N Terminus And The Rrm Domain Of P34 And Tmentioning
confidence: 98%
See 2 more Smart Citations
“…Immunoprecipitations were performed as previously described (24). Protein A-labeled magnetic beads (Dynabeads, Life Technologies) were blocked in phosphate-buffered saline (PBS)-bovine serum albumin and incubated with anti-P34/P37 or anti-L5 antibody for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%